A Quasi‐experimental Outcomes Analysis of a Psychoeducation Intervention for Pregnant Women with Abuse‐related Posttraumatic Stress. Issue 3 (22nd April 2014) - Rowe, Heather; Sperlich, Mickey; Cameron, Heather; Seng, Julia
ABSTRACT Objective To test the effectiveness of a trauma‐specific, psychoeducational intervention for pregnant women with a history of childhood maltreatment on six intrapartum and postpartum psychological outcomes. Design Quasi‐experimental study comparing women from a single‐group, pretest–posttest pilot intervention study with women matched from a prospective observational study. Setting Rural and university‐based prenatal clinics. Participants Pregnant women entered the study by responding to an advertisement or by referral from a maternity care provider. Women could take part whether or not they met posttraumatic stress disorder diagnostic criteria. Outcomes data exist for 17 pilot intervention study participants and 43 matched observational study participants. Interventions Participants in the observational study received usual care. Participants in the pilot intervention study received usual care plus the intervention, a fully manualized, self‐study program supported by weekly phone tutoring sessions with a health professional. Main Outcome Measures The National Women's Study PTSD Module, the Peritraumatic Dissociation Experience Questionnaire, the Perception of Care Questionnaire, the Postpartum Depression Screening Scale, the Postpartum Bonding Questionnaire, and a semantic differential appraisal of the labor experience. Results Participants in the intervention study had better scores on all measures. Differences in means between participants in the intervention study and participants in the observational study equated to medium effect sized for dissociation during labor, rating of labor experience, and perception of care in labor and small effect sizes for postpartum posttraumatic stress disorder (PTSD) symptoms, postpartum depression symptoms, and motherinfant bonding. Conclusion This trauma‐specific intervention reaches and benefits pregnant women with a history of childhood maltreatment.